2017
DOI: 10.1016/j.medici.2016.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Response inhibition, set shifting, and complex executive function in patients with chronic lower back pain

Abstract: We found no statistically significant difference in response inhibition, set shifting, or complex executive function between CLBP patients and healthy older adults. Moreover, a risky decision-making pattern found in the Lithuanian population may underscore the importance of cultural context when examining complex executive function. However, further studies are needed to prove this point.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 45 publications
1
28
0
3
Order By: Relevance
“…As part of the maladaptive neuroplastic response to pain in endometriosis, P3a findings here may reflect similar recruitment of additional neural resources, particularly in relation to stimulus evaluation, attentional processing, and/or perhaps most of all, inhibitory demands (Bruin and Wijers, 2002;Donkers and Van Boxtel, 2004;Ramautar et al, 2004;Polich, 2007;Smith et al, 2008). Although there was no difference in task performance between groups that would reflect behavioral inhibition difficulties (e.g., commission errors), as with other studies (Glass et al, 2011;Veldhuijzen et al, 2012;Berryman et al, 2014;Masiliünas et al, 2017), P3a findings indicate that a wide range of neuronal substrates of inhibitory control are less active overall in women with endometriosis and CPP compared to HCs. No differences were noted for the non-target SW.…”
Section: Discussionsupporting
confidence: 77%
“…As part of the maladaptive neuroplastic response to pain in endometriosis, P3a findings here may reflect similar recruitment of additional neural resources, particularly in relation to stimulus evaluation, attentional processing, and/or perhaps most of all, inhibitory demands (Bruin and Wijers, 2002;Donkers and Van Boxtel, 2004;Ramautar et al, 2004;Polich, 2007;Smith et al, 2008). Although there was no difference in task performance between groups that would reflect behavioral inhibition difficulties (e.g., commission errors), as with other studies (Glass et al, 2011;Veldhuijzen et al, 2012;Berryman et al, 2014;Masiliünas et al, 2017), P3a findings indicate that a wide range of neuronal substrates of inhibitory control are less active overall in women with endometriosis and CPP compared to HCs. No differences were noted for the non-target SW.…”
Section: Discussionsupporting
confidence: 77%
“…En segundo lugar, la diversidad de funciones ejecutivas dificulta establecer una relación unidimensional con el dolor, razón por la que parece oportuno optar por medidas ecológicas de las funciones ejecutivas que consideren a estas desde un punto de vista holístico. En tercer lugar, aunque no lo abordaremos aquí por exceder el propósito de este artículo, habría que tener en cuenta otras variables mediadoras, tales como la medicación o el sueño, a la hora de analizar los factores mediadores entre la severidad del autismo y la percepción del dolor (Masiliūnas et al, 2017).…”
Section: Introductionunclassified
“…In most studies, participants with fibromyalgia been diagnosed prior to their recruitment [ 43 , 47 , 49 , 50 , 51 , 52 , 55 ]; the disease onset, when specified, is reported in Table 2 . Only one study [ 54 ] included subjects with generic chronic pain, nine of whom were indicated as having fibromyalgia according to criteria of the American College of Rheumatology Criteria for the Classification of Fibromyalgia [ 3 ]. In all cases presented in this review, an assessment of pain or its impact on the individual’s abilities or life was performed (see Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…In all cases presented in this review, an assessment of pain or its impact on the individual’s abilities or life was performed (see Table 2 ). Four studies [ 49 , 51 , 52 , 54 ] adopted the visual analogue scale to measure the level of pain experienced by patients on a continuum from “none” to an “extreme amount of pain” [ 56 ]. A similar instrument, the numeric rating scale, was employed in two studies [ 47 , 50 ] to provide a measure of pain on a scale from 0 to 10, where 0 represents “no pain” and 10 represents “the worst pain possible” [ 57 ].…”
Section: Resultsmentioning
confidence: 99%